Dampak Implementasi Sustainable Tourism dalam Kerjasama Indonesia-Swiss terhadap Sektor Pariwisata Tana Toraja - Handana, Grace Mase'; Burhan, Zulkhair; Mamma, Beche Bt. (Universitas Bosowa, 2025)
This study aims to describe the impact of sustainable tourism implementation in the cooperation between Indonesia and Switzerland on the tourism sector in Tana Toraja Regency. The program, carried out by Swisscontact, a non-governmental organization that supports developing countries, focuses on promoting sustainable tourism as a means of sectoral development. Using descriptive qualitative methods, the study finds that the impacts of sustainable tourism in Tana Toraja can be observed in three main aspects: economic, environmental, and socio-cultural. Economically, the program has improved the capacity of local people to market products and generate income, although the COVID-19 pandemic significantly reduced tourist arrivals and limited economic benefits. Environmentally, the initiative has contributed to maintaining cleanliness and reducing waste. Socio-culturally, it has increased local awareness of the importance of conserving cultural heritage and local wisdom.